Extraosseous chondrosarcoma: a descriptive study from 1983 to 1998 at the Brazilian National Cancer Institute - Meohas, Walter (2002)
These tumors are uncommon, but in view of the relatively large number of cases we performed a retrospective review of all our cases at INCA, between 1983 and 1998. We looked at epidemiological factors - prevalence, age, sex and race. We also studied the type of treatment and results - metastasis and disease free survival.